TARIQAH MUBASYARAH UNTUK PENINGKATAN KOMPETENSI MAHRATUL KALAM PEMBELAJARAN BAHASA ARAB MA DARUSSALAM SENGKUBANG - Lukman Hakim, Bahtiar; Suriadi, Suriadi; Irawan , Deni (ILJ: Islamic Learning Journal, 2024)
This study departs from the phenomenon of Arabic language learning in class X of Madrasah Aliyah Darussalam using ?ar?qah Mub?syarah, students in the class consist of different school inputs who have different basic Arabic language skills, besides that the Arabic teacher's background is not a graduate of Arabic Language Education. This study discusses how the lesson plan, implementation and evaluation and what are the implications for improving Mah?ratul Kal?m. This research is a field research with a qualitative approach, the type of research is phenomenology with descriptive methods. Data collection techniques through interviews, observation and documentation. Data analysis uses an inductive model which includes data reduction, data display and data verification, while checking the validity of the data is done with observation persistence, triangulation and member check. The results of this study show that Arabic language learning at Madrasah Aliyah Darussalam focuses on mastering speaking competence by using ?ar?qah Mub?syarah in the form of implementation: planning in the form of learning tools which include objectives, materials, learning resources, student characters and methods.  learning implementation consists of pre-learning, core learning and end-of-learning activities, learning evaluation contains student learning evaluation results. learning implications on improving speaking skills that have an impact on creating a language environment and developing Islamic understanding